Non-Thrombogenicity of Clean Glass Revealed by Native Whole Blood Assay in Bead Columns - Bergeron, J A; DiNovo, J M; Razzano, A F; Dodds, W J (Thrombosis and Haemostasis, 1983)
The previously described native whole blood assay for materials in solution or suspension has been adapted to materials in a bead column configuration. These experiments showed that the glass itself accounts for little or none of the high blood-reactivity observed with conventional glass bead columns. Columns composed solely of soft glass that was “cleaned” by heat treatment (500-595° C 18 hr, electric oven) were benign toward flowing native whole blood for all variables measured (platelet count and platelet-free plasma [C14]-serotonin content, platelet factor 3 and factor XII activities, and recalcification time) with the standard contact protocol. In addition, the effluent successfully maintained perfusion of the isolated kidney, a measure of the ability of platelets to support vascular integrity. Prolonged (30 min) normothermic contact with titrated whole blood increased the subsequent reactivity of initially clean glass toward whole blood albeit to a level much less than that of conventional glass bead columns.
Keywords: Non-thrombogenicity; Glass beads; Native blood assay